Liquefied Petroleum Gas Poisoning in a Child: A Case Report from a Low-Middle Income Country - Abid Jamali; Latif Shamasuddin; Aimen Yunus; Nadeem Ullah Khan (Asia Pacific Journal of Medical Toxicology)
Introduction: Liquefied Petroleum Gas (LPG) is primarily a mixture of propane and butane, and in Pakistan, it typically contains 95-100% propane. With the increasing use of LPG, a rise in poisoning cases has been observed.Case report: We are reporting the case of a 5-year-old male who presented to the pediatric emergency department with unconsciousness lasting approximately 30 minutes after being found near an LPG cylinder in the kitchen. Upon arrival, the patient was tachycardic, with a Glasgow Coma Scale (GCS) score of 11/15. The systemic examination was unremarkable, and the electrocardiogram (ECG) showed a normal sinus rhythm. However, troponin-I levels were elevated at 135 ng/L (normal range: 0-57 ng/L), and blood gases revealed mild acidosis with bicarbonate levels of 16.8. A repeat troponin-I measurement showed a significant increase to 749 ng/L, prompting initiation of inotropic support with epinephrine. After 12 hours, troponin-I levels began to decrease. The patient remained in the Pediatric Intensive Care Unit (PICU) for 36 hours before being discharged in stable condition.Discussion: Propane gas is heavier than air, causing it to flow along the floors. It acts as an asphyxiating gas, displacing oxygen in the lungs and making breathing difficult. Propane primarily affects the respiratory, nervous, and cardiovascular systems.Conclusion: This case highlights the importance of admitting children exposed to LPG to higher care units for close monitoring, as initial cardiac enzyme levels and ECG may appear normal but can rapidly worsen. Serial monitoring of cardiac enzymes and electrocardiograms is crucial to prevent lethal arrhythmias and cardiac dysfunction.